THE INFLUENCE OF JOB SATISFACTION, JOB STRESS, JOB INSECURITY, ROLE CONFLICT ON TURNOVER INTENTION - ANUGRAHENI, NATASYA RISZI; FARIDA, IDA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
The purpose of this research is to determine the influence of job satisfaction, job stress, job insecurity, and role conflict on turnover intention of employees at PT.XXX. The population used was 76 employees using a saturated sampling technique, namely taking the entire population to be used as a sample. The number of samples in this study was 76 employees, the data collection technique uses questionnaire distribution with a Likert scale. The analysis technique used is multiple linear regression. Based on the results of hypothesis testing data analysis in this study, job datisfaction gas an effect on turnover intention, job stress has no effect on turnover intention, job insecurity has no effect on turnover intention, and role conflict has an effect on turnover intention.